Mechanical properties of ceramic tiles by replacement of quartz by RHA and POFA - Jamo, Hassan Usman (2015)
Rice husk ash (RHA) and palm oil fuel ash (POFA) have a great potential to replace the quartz element in porcelain composition. RHA and POFA were mostly used by construction industries, and only a few researchers studied its applications in ceramics industries. It is due to the mechanical properties of porcelain are strongly affected by the generated thermal stress during processing because of the deleterious effects of quartz. In this work, the quartz is being replaced by RHA, POFA and the combination of RHA and POFA. The sample's composition was mixed for 90 minutes and pressed at different mold pressures (31, 61, 91 and 121 MPa) and then sintered at the sintering temperatures ranging from 1000 to 1300 οC at different soaking times ranging from 1 to 3 hours respectively. The samples were measured the physical and mechanical properties and then the microstructure observation. It was found that the RHA, POFA and the combination of RHA and POFA have tremendous effects on the properties of porcelain tiles. For the RHA, the highest bulk density (2.42 g/cm3) and compressive strength (44 MPa) were recorded on 20 wt% of RHA at the sintering temperature of 1200 οC and the soaking time of 2 hours. For the POFA, the highest bulk density (2.45 g/cm3) and compressive strength (46 MPa) were achieved on 15 wt% of POFA at the sintering temperature of 1100 οC and the soaking time of 2 hours. For the combination of RHA and POFA, the highest bulk density (2.43 g/cm3) and compressive strength (45 MPa) were recorded on 20 wt% of RHA and POFA at the sintering temperature of 1200 οC and the soaking time of 2 hours. It was observed that the microstructure was enhanced by increasing the sintering temperature, mould pressure and soaking time. It can be concluded that samples containing POFA attained vitrification stage at lower temperature and exhibited higher mechanical properties. Thermal expansion and thermal conductivity measurement are some of the areas that could be explored for further research.